1993
DOI: 10.1164/ajrccm/148.5.1226
|View full text |Cite
|
Sign up to set email alerts
|

Airway Inflammation in Smokers with Nonobstructive and Obstructive Chronic Bronchitis

Abstract: To assess the manifestation and location of airway inflammation in smokers with chronic bronchitis (CB) or chronic obstructive pulmonary disease (COPD), we lavaged the airways of 12 smokers with CB and 11 smokers with COPD and coexisting CB (OCB). For comparison, the airways of 5 asymptomatic smokers (AS) and 10 healthy nonsmokers (HNS) were lavaged. In all cases, the first lavage aliquot, labeled "bronchial lavage" (BL), was processed separately from the four subsequent aliquots, which were combined and label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
2
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 20 publications
9
101
2
1
Order By: Relevance
“…The pathogenesis of COPD is characterized by neutrophil infiltration of pulmonary tissues and elevated concentrations of MPO in bronchoalveolar lavage fluids 18 . MPO is the only enzyme in the body that is known to produce hypochlorous acid, which oxidizes lipids, proteins and DNA 3,4 .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of COPD is characterized by neutrophil infiltration of pulmonary tissues and elevated concentrations of MPO in bronchoalveolar lavage fluids 18 . MPO is the only enzyme in the body that is known to produce hypochlorous acid, which oxidizes lipids, proteins and DNA 3,4 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that GSH plays a critical role in maintaining epithelial membrane integrity and may protect epithelial cells against the inflammatory response produced by either inhaled or endogenous oxidants/free radicals. Furthermore, LINDEN and coworkers [204,205] demonstrated that airway obstruction, measured by means of the forced expiratory volume in one second (FEV1) in patients with COPD, correlated significantly with the concentration of GSH in BALF; the higher the BALF GSH, the lower the FEV1. It may be that the BALF GSH levels were influenced by the recent smoking history of these patients [24].…”
Section: Antioxidant Protective Genesmentioning
confidence: 99%
“…For example, higher numbers of neutrophils, macrophages and CD8 positive T-cells in the peripheral airways of COPD patients were found as compared to smokers [10,[17][18][19], whereas others did not [10,19,20]. Two studies showed a higher percentage of neutrophils and higher IL-8 levels in broncho-alveolar lavage of COPD patients [13,21], whereas Linden et al found no differences [7]. A few studies showed higher numbers of neutrophils [22], CD3, CD4 [23] CD8 positive T-cells [23,24] in bronchial biopsies, whereas other studies found no differences in neutrophils [24], CD3, CD4 [22,24] and CD8 positive T-cels [22], macrophages, eosinophils and mast cells [22,24].…”
Section: Introductionmentioning
confidence: 95%
“…For example, higher numbers of CD8 positive T-cells, macrophages, neutrophils, and mast cells, both in central and peripheral airways have been found in COPD patients, irrespective whether these patients were current smokers or ex-smokers [4][5][6][7][8][9][10]. In addition, the percentage of neutrophils and IL-8 levels in sputum and broncho-alveolar lavage of COPD patients were higher [7,[11][12][13][14][15][16]. As compared to healthy smokers, the differences with COPD patients are less clear cut.…”
Section: Introductionmentioning
confidence: 99%